Peripartum Cardiomyopathy: a Life Threatening Obstetric Emergency (Faridpur Medical College Journal, 2019)
Peripartum cardiomyopathy (PPCM) is a rare, life-threatening heart disease of unclear origin and is characterized by heart failure of sudden onset between the final weeks of pregnancy and 5 months after delivery. Incidence varies over geography and ethnicity. Risk factors include advanced maternal age, multiparity, preeclampsia, multiple pregnancy, anaemia, and so many other causes. PPCM is often not diagnosed until late in its course, because of its clinical manifestations are highly variable and a heart disease may not be suspected at first. Frequent presenting symptoms of PPCM, such as lassitude, shortness of breath on mild exertion and coughing are often initially misinterpreted as evidence of pneumonia or as physiological accompaniments of pregnancy and delivery. The clinical picture of PPCM corresponds to a dilated cardiomyopathy (DCM) with signs of severe heart failure. Medical management is similar to other causes of systolic heart failure, except for the ACE inhibitors and angiotensin receptor blockers are avoided in pregnancy. As there are lots of physiological changes during pregnancy and immediately after delivery, it is usually difficult to measure PPCM effectively. Complications include cardiac arrhythmia, thromboembolism, and refractory heart failure. Maternal deaths are not uncommon. Recently the role of abnormal prolactin metabolism and resulting myocardial toxicity have been explored and bromocriptine has shown promise as a potential treatment option.Faridpur Med. Coll. J. Jul 2018;13(2): 93-96